Counter-protest: young people’s political engagement - Lieberkind, Jonas (Politica, 2021)
Based on The International Civic and Citizenship Education Study as well as a qualitative study of Danish young people born in the early 00s, the article explores and discusses their political engagement both empirically and theoretically. The two studies show that Danish youths possess an extensive political interest and knowledge of the democratic society, but at the same time, they articulate a prevalent reservation about protesting and participating in public political activities. The argument of the article is that their form of political engagement can analytically be reflected as a counter-protest. The term counter-protest captures an increasing political engagement, but an engagement that counteracts protest as a relevant form of political action and, furthermore, supports the conventional political system.